Assessing the feasibility of a randomised controlled trial examining the effect of hearing aids on cognitive decline in elderly individuals: a study protocol - Inge Stegeman; Adriana L Smit; Denise Fuchten; Irene M C Huenges Wajer; Koen S Rhebergen (BMJ Open)
Introduction Hearing loss is one of the leading potentially modifiable risk factors for dementia. There is growing evidence suggesting that treating hearing loss with hearing aids could be a relatively low-cost intervention in reducing cognitive decline and the risk of dementia in the long term. However, given the current constraints of the limited evidence, it is premature to draw definitive conclusions about the effect of hearing aids on cognitive functioning. More long-term randomised studies examining this effect would be recommended. Prior to embarking on large-scale lengthy randomised controlled trials (RCTs), it is imperative to determine the viability of such studies. Therefore, the purpose of the current study is to assess the feasibility of a RCT that investigates the effect of hearing aids on cognitive functioning in elderly hearing impaired individuals.Methods and analysis In this randomised controlled feasibility trial, 24 individuals aged 65 years or older with mild to moderate hearing loss (≥35–<50 dB pure tone average (0.5–4 kHz) unilateral or bilateral) will be included and randomised towards a hearing aid intervention or no intervention. At baseline and at 6-month follow-up, a test battery consisting of cognitive tests and questionnaires will be administered to both groups. The primary outcome of the study is the willingness of hearing impaired individuals to be randomised for hearing amplification in a study regarding cognition. The secondary outcomes are the feasibility of the test battery and the therapy compliance of hearing aid use.Ethics and dissemination This research protocol was approved by the Institutional Review Board of the University Medical Centre Utrecht (NL80594.041.22, V.3, January 2023). The trial results will be made accessible to the public in a peer-reviewed journal.Trial registration number ISRCTN84550071.